ANALISIS SISTEM PENYELENGGARAAN MAKANAN, POLA MAKAN, TINGKAT KONSUMSI ZAT GIZI DAN STATUS GIZI ANAK DI PANTI ASUHAN SONAF MANEKA KOTA KUPANG - Anita Christina Sembiring; Maria Helena Dua Nita; Astuti Nur; Meirina Sulastri Loaloka (Poltekkes Kemenkes Kupang, 2022)
This study aims to analyze the food administration system, diet, nutrient consumption level and nutritional status of children at the Sonaf Maneka Orphanage, Kupang City. This research is descriptive analytic because it analyzes the level of nutritional consumption and nutritional status of the respondents, it is also observational because it is carried out using interviews and direct observations of respondents with the help of a questionnaire. The research was conducted in May 2021 at the Sonaf Manekat Orphanage, Kupang City. The population in this study were all children in the Sonaf Manekat Orphanage, Kupang City. The sample in this study were all children in the Sonaf Maneka Orphanage who were willing to be respondents and were at the research location at the time of the research. Sample characteristics such as name, age, gender were collected by means of interviews with caregivers. Data about the food administration system was obtained by means of direct interviews with the Orphanage Manager. Dietary data were collected using the FFQ (Food Frequency Questionnaire) Form by interviewing respondents who were already in school and through direct observation or interviews with caregivers to respondents who were not yet in school. Data on the level of nutrient consumption was collected using the Food Recall form 1x24 hours by interviewing respondents who were already in school and through direct observation or interviews with caregivers to respondents who were not yet in school. Nutritional status data were collected by means of anthropometric measurements based on the index of TB/U, BW/PB and BMI/U carried out by researchers. Data about diet will be processed using the Excel program, data on the level of nutrient consumption that has been collected will be processed using the nutrisurvey application and will be compared with the Nutrition Adequacy Rate (RDA), the nutritional status data of respondents will be processed using the WHO-Antro application. The processed data will be analyzed descriptively and presented in the form of narration and tabulation. The food delivery system at the Sonaf Maneka orphanage is social or non-commercial. The diet of children at the Sonaf Maneka orphanage is dominated by carbohydrates, namely rice and noodles. The level of consumption of energy, protein and fat in children at the Sonaf Maneka orphanage is still very low. Most of the children's nutritional status in the Sonaf Maneka orphanage has normal nutritional status